The sword and the shield the Mitrokhin Archive and the secret history of the KGB - Andrew, Christopher M. (Basic Books, 1999)
Describes a treasure trove of secret documents found by the FBI, and offers facts about every country in the world, as well as information that contributes to the history of the last century.